A construção da imagem de Otávio, Cleópatra e Marco Antônio entre moedas e poemas (44 a 27 a.C.) - Silva, Camilla Ferreira Paulino da (2014)
This work originated from a study on how Octavian, before obtaining the title of Augustus, in 27 b.C., reframed his image and became the first emperor of Rome. This study also dealt with how Octavian built a stigmatized image of Cleopatra and Mark Antony, his rivals during the final period of the civil war. Investigating the period that goes from 44 (assassination of Julius Caesar) to 27 b.C. (which historiography conventionally marks as the beginning of the Principate), we analyzed Octavius’ effort to legitimize himself as an ideal Roman, follower and rescuer of the ancient traditions, through the use of imagetic representation that praises Octavian while stigmatizes the Egyptian queen and Antony. Accordingly, we directed our gaze to the poems of Quintus Horatius Flaccus, which allowed us to associate the images he built with those Octavian tried to convey publicly. To recover the official image that Octavian strived to establish, we also investigated a corpus of coins that references himself as adopted son of Julius Caesar, among other glorious attributes. We also investigated a set of coins in which Cleopatra and Mark Antony are depicted, trying to reconstruct the representation that they intended for themselves, presenting a different image from the one that Octavius and his supporters built for the couple. The theoretical tools we used in this research come from the concepts of representation, by Roger Chartier, and symbolic power, by Pierre Bourdieu, and also some discussion about image and its use for the consolidation of authorities by Gian Paolo Caprettini. The methodology used was Laurence Bardin's content analysis.